(3) \( \frac{\left(2 \times 10^{2}\right)^{3}\left(6 \times 10^{-2}\right)^{2}}{\left(2 \times 10^{-2}\right)\left(3 \times 10^{4}\right)^{2}}= \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Bonus Knowledge
To solve the expression, we can first simplify each component step by step. 1. Calculate each term: - \( \left(2 \times 10^{2}\right)^{3} = 2^{3} \times (10^{2})^{3} = 8 \times 10^{6} \) - \( \left(6 \times 10^{-2}\right)^{2} = 6^{2} \times (10^{-2})^{2} = 36 \times 10^{-4} \) - \( \left(2 \times 10^{-2}\right) = 2 \times 10^{-2} \) - \( \left(3 \times 10^{4}\right)^{2} = 3^{2} \times (10^{4})^{2} = 9 \times 10^{8} \) 2. Putting it all together: \[ \frac{\left(2 \times 10^{2}\right)^{3}\left(6 \times 10^{-2}\right)^{2}}{\left(2 \times 10^{-2}\right)\left(3 \times 10^{4}\right)^{2}} = \frac{(8 \times 10^{6})(36 \times 10^{-4})}{(2 \times 10^{-2})(9 \times 10^{8})} \] 3. Multiply the numerator: \[ 8 \times 36 = 288 \quad \text{and} \quad 10^{6} \times 10^{-4} = 10^{2} \] So, the numerator becomes \( 288 \times 10^{2} \). 4. Multiply the denominator: \[ 2 \times 9 = 18 \quad \text{and} \quad 10^{-2} \times 10^{8} = 10^{6} \] So, the denominator becomes \( 18 \times 10^{6} \). 5. Now we have the expression: \[ \frac{288 \times 10^{2}}{18 \times 10^{6}} = \frac{288}{18} \times \frac{10^{2}}{10^{6}} \] 6. Calculate \( \frac{288}{18} = 16 \) and \( \frac{10^{2}}{10^{6}} = 10^{-4} \). 7. Therefore, the result is: \[ 16 \times 10^{-4} = 1.6 \times 10^{-3} \] The final answer is: \[ \boxed{1.6 \times 10^{-3}} \]